Optimalisasi Pengelolaan Sampah di Indonesia: Integrasi Teknologi Digital, Pengawasan Hukum, dan Mitigasi Pencemaran Lingkungan Menuju Pembangunan Berkelanjutan - Nayla Syalluna; Safira Aulia; Dewy Sulistyowati; Danang Hannanto; Muhammad Adymas Hikal Fikri (PT. Hasba Edukasi Mandiri, 2026)
Waste management in Indonesia remains a multidimensional challenge, exacerbated by population growth, rapid urbanization, and increasing consumption patterns. This study aims to analyze the integration of digital technology in optimizing a circular economy-based waste management system, and to examine the effectiveness of the legal framework and environmental oversight in addressing pollution caused by inadequate waste management practices in Indonesia. A normative juridical method was employed, utilizing statutory and conceptual approaches alongside qualitative descriptive data analysis. The findings indicate that digital technologies including the Internet of Things (IoT), Android-based waste marketplace applications, and machine learning-driven data analytics, hold significant potential to accelerate the transition toward a circular economy, though their adoption remains constrained by the digital divide and infrastructural limitations. From a legal standpoint, Indonesia's regulatory framework under Law No. 18 of 2008 and Law No. 32 of 2009 is relatively comprehensive, yet its effectiveness is undermined by inconsistent implementation, weak inter-agency coordination, and insufficient law enforcement. This study recommends a multi-stakeholder integration model grounded in the Penta Helix framework, combining digital innovation, robust legal oversight, and environmental pollution mitigation as a cohesive strategy toward sustainable development in Indonesia.